Evaluation of work ethic, motivation, competence, capability, and integrity of members of the seaweed cooperative (Gracilaria sp.) Agar Sentosa Makmur, Sidoarjo Regency - Tryono, Agus; Istiqomah, Titis; Soedrijanto, Angky; Sudarmono, Heri (Lempuk: Jurnal Ilmu Kelautan dan Perikanan, 2025)
The work behavior of seaweed cooperative members must demonstrate high performance. Seaweed, as one of the national strategic products being promoted by the Indonesian Government, must be able to compete as a high-quality export product in the global market. This study aims to evaluate the performance of seaweed cooperative members (Gracillaria sp.) in terms of developing work ethic, motivation, competence, capability, and integrity in seaweed cultivation in Sidoarjo Regency. A descriptive study using an empirical survey approach was conducted on members of the Agar Sentosa Makmur seaweed cooperative in Sidoarjo Regency. Data were collected through in-depth interviews. The interview results were weighted on a scale of 1-10 and analyzed using statistical tools to determine the correlation between the variables studied. The results showed that the cooperative members' capabilities in cultivation were high. This level of capability still needs to be balanced by improving their competence.